Fahr’s syndrome in teenage girls with systemic lupus erythematosus: A case report - Damar Prasetya; Sumadiono Sumadiono (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Fahr’s disease or Fahr’s syndrome is a condition characterized by intracranial calcifications especially in basal ganglia and dentate nuclei. They are a rare condition with a broad range of manifestations from asymptomatic condition to severe neurological and psychiatry signs and symptoms. The aim of this report to present Fahr’s syndrome as an alternative diagnosis of neuropsychiatry symptoms in systemic lupus erythematosus (SLE) patients. We present a 17-year-old teenage girl who have had a preexisting diagnosis of SLE and have been on remission. The patient recently had experienced headache, auditory hallucination and memory loss despite having a low activity score of SLE and no laboratory relapse. Head CT scan showed bilateral basal ganglia calcifications suggesting a Fahr’s disease. Clinical outcome in this condition might vary but might worsen neurocognitive functions.